2014
DOI: 10.1159/000369558
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Salt Diet Increases the Estimated Net Endogenous Acid Production in Nondiabetic Chronic Kidney Disease Patients Treated with Angiotensin Receptor Blockade

Abstract: Background/Aims: An acid-base imbalance precedes renal disease progression in patients with chronic kidney disease (CKD). Little is known about the effects of a low-salt diet (LSD) on net endogenous acid production (NEAP) levels in CKD patients using angiotensin receptor blockade. Methods: We enrolled a total of 202 nondiabetic CKD patients who underwent an 8-week treatment with olmesartan from the original trial [Effects of Low Sodium Intake on the Antiproteinuric Efficacy of Olmesartan in Hypertensive Patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…In line with this study, a prospective cohort study, Chan et al found that higher NEAP is associated with more muscle loss among 3122 older adults [22]. Many studies have shown an inverse effect of sodium intake on NEAP, as in the as present study [55]. Fruits and vegetables are known as the main sources of buffer in the diet due to their potassium content, which helps electro-neutrality through exchange with hydrogen ions in the distal part of the nephron [56].…”
Section: Discussionsupporting
confidence: 89%
“…In line with this study, a prospective cohort study, Chan et al found that higher NEAP is associated with more muscle loss among 3122 older adults [22]. Many studies have shown an inverse effect of sodium intake on NEAP, as in the as present study [55]. Fruits and vegetables are known as the main sources of buffer in the diet due to their potassium content, which helps electro-neutrality through exchange with hydrogen ions in the distal part of the nephron [56].…”
Section: Discussionsupporting
confidence: 89%